2012
DOI: 10.3892/ijmm.2012.1042
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 and IGF-1 influence the re-differentiation capacity of human chondrocytes in 3D pellet cultures in relation to different oxygen concentrations

Abstract: To prevent de-differentiation of chondrocytes in vitro, the 3D environment, growth factors and different oxygen concentrations were considered. In this in vitro study, we quantified the influence of insulin-like growth factor (IGF)-1 and/or transforming growth factor (TGF)-β1 under differing oxygen (5/21% O(2)) levels on the proliferation and synthesis rates of hyaline extracellular matrix (ECM) components in chondrogenic pellet cultures. Human chondrocytes isolated from articular cartilage were transferred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…This was observed for both oxygen conditions, but was more pronounced under hypoxia. This finding suggests an additive effect of both growth factors, which was also observed in previous studies (23) as well as by other research groups (18,32,33). Additionally, it was previously reported that intracellular signalling pathways of TGF-β1 and IGF-1 are partially linked (7,34).…”
Section: Discussionsupporting
confidence: 91%
“…This was observed for both oxygen conditions, but was more pronounced under hypoxia. This finding suggests an additive effect of both growth factors, which was also observed in previous studies (23) as well as by other research groups (18,32,33). Additionally, it was previously reported that intracellular signalling pathways of TGF-β1 and IGF-1 are partially linked (7,34).…”
Section: Discussionsupporting
confidence: 91%
“…As a preliminary prove of the protocols’ efficiency, we considered gene expression analysis as the best option, since it is affordable and the required instrumentation (PCR, inverted optical microscope) is most likely available in most cell biology laboratories. The set of analysed genes was carefully chosen considering the available literature to monitor cartilage phenotype alterations (Caterson et al, 2001; Diekman et al, 2010; Grogan et al, 2014; Jonitz et al, 2012; Seda Tigli et al, 2009; Shi et al, 2014). Based on the mentioned, the correlation between COL2 and COL1 in addition to ACAN, seemed to be the most suitable.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent in vitro studies indicate that the most efficient chondrogenic differentiation of chondrocyte-like progenitor cells and mesenchymal stem cells is achieved by using standard cell culture medium supplemented with growth factors like insulin-like growth factor (IGF) 1, transforming growth factor (TGF) β1 and 2, fibroblast growth factor (FGF) 2, and bone morphogenetic protein (BMP) 2. [4][5][6] It is known that IGF-1 enhances the synthesis of proteoglycans and directly decreases the degradation of proteoglycans in cartilage. 7 Moreover, it was shown that IGF-1 helps to maintain the survival of chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the clinical application for cartilage repair, cells have been incubated in three-dimensional culture systems, like pellets and microspheres, 4,14 as well as hydrogels or biomaterials. [15][16][17][18] Superficial cartilage defects have mainly been treated with hyaluronic acid (HA), while chondral and osteochondral lesions have been medicated by means of HA and autologous cartilage transplantation (ACT) since 1994.…”
Section: Introductionmentioning
confidence: 99%